Varian Islam Nusantara: Jawa, Minangkabau dan Gorontalo - Donald Qomaidiansyah Tungkagi (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2017)
This article discusses how the encounter of Islam and culture in Indonesia, and how Islam on one hand affects culture and on the other hand it is influenced by culture. The encounter between Islam and local culture has formed a new habitat that is later called the Islamic Nusantara tradition. The findings in this article prove that the interaction of Islam with local culture occurs in a socio-historical context influenced by the pattern of the spread of Islam in the archipelago. By using the theory of Taufik Abdullah in this article the author compares the three variants of Islamic Nusantara with the pattern and uniqueness of each form: a) Javanese variant, there is a process of acculturation between Islam and culture which are equally strong. The Javanese Islamic variant describes the result of a reconciliation process between identity, belief and the style of Javanese and Islam as